Poly(ethylene glycol)-Lipid-Conjugated Antibodies Enhance Dendritic Cell Phagocytosis of Apoptotic Cancer Cells - Teruyuki Nagamune; Satoshi Takamori; Satoshi Yamaguchi; Yoichiro Sugimoto; Urara Tomita (MDPI AG, 2012)
A simple method for attaching immunoglobulin G (IgG) on the cell surface was successfully developed for enhancing phagocytosis of apoptotic tumor cells (ATCs) by dendritic cells (DCs) ex vivo. By conjugating with a poly(ethylene glycol) (PEG)-lipid, named the biocompatible anchor for the membrane (BAM), arbitrary IgG could be incorporated into the cell membrane. In particular, when IgG-BAM conjugates were prepared at the optimal molar ratio of IgG to BAM (1 to 20), almost all cells were efficiently modified with IgG by treatment with IgG-BAM. This simple method was successfully applied to four types of mammalian cells. Furthermore, treatment of ATCs with the IgG-BAM conjugate increased the phagocytosis ratio of ATCs by DCs two-fold when compared to no treatment. This phagocytosis-enhancing effect was nearly identical to treatment with a tumor-specific IgG. Thus, without employing the tumor-specific IgG, which is difficult to obtain for any tumor cells and is expensive, the present method could opsonize ATC with the use of arbitrary IgG. The results strongly indicate that IgG-BAM treatment represents a promising method for opsonizing ATC with human serum IgG, and that this approach will lead to objective clinical responses in DC vaccines.